PENGENDALIAN ANGGARAN YANG KETAT DAN ORIENTASI WAKTU SEBAGAI PEMODERASI PENGARUH ANGGARAN PARTISIPATIF PADA SENJANGAN ANGGARAN - Puji Astuti, Sang Ayu Putu; Wirama, Dewa Gede; Rasmini, Ni Ketut (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2017)
Previous researches concerning the influence of participatory budgeting on budgetary slack found inconsistent results. The purpose of this research is to determine the influence of participatory budgeting on budgetary slack with tight budgetary control and time orientation as moderating variables in Gianyar local government SKPD’s. Data was collected by the use of questionnaires and respondents were selected by purposive sampling method. The analysis technique used are simple regression and moderated regression analysis. The result of analysis shows that participatory budgeting had no positive effect on budgetary slack, tight budgetary control weaken the influence of participatory budgeting on budgetary slack, and  time orientation does not  moderate the influence of participatory budgeting on budgetary slack
Keywords: budgetary slack, participatory budgeting, tight budgetary control, time orientation.